Positive electrode sheet, battery and preparation method thereof

By introducing lithium-rich compounds and an optimized positive electrode active material layer into the positive electrode sheet of the lithium-ion battery, the performance bottlenecks of traditional LFP materials in low temperature and fast charging are solved, and lithium-ion batteries with high energy density, good low temperature performance and strong fast charging capabilities are achieved.

CN119764345APending Publication Date: 2025-04-04中汽新能(天津)电池科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963772.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Traditional lithium iron phosphate (LFP) materials have bottlenecks in low-temperature performance and fast charging, limiting their application in fast charging and low-temperature environments.

Method used

A positive electrode sheet is adopted, including a positive electrode active material layer arranged on both sides of the positive electrode current collector, which is composed of lithium iron phosphate, lithium rich compound, conductive agent, binder and dispersant. By optimizing the proportion and combination of these materials, the conductivity and stability of the electrode are improved.

Benefits of technology

It realizes the high available energy in low temperature environments, supports 3C fast charging, and the capacity retention rate of 800 cycles is above 93%, improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764345A_ABST
    Figure CN119764345A_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of lithium-ion batteries, and specifically relates to a positive electrode sheet, a battery and a preparation method thereof. The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer arranged on both sides of the positive electrode current collector; the positive electrode active material layer includes a positive electrode active material, a lithium-rich compound, a positive electrode conductive agent, a positive electrode binder and a positive electrode dispersant. The implementation scheme of the present application improves the cycle life and reduces the impedance through the application of lithium-rich compounds, and improves the homogenization effect through the application of positive electrode dispersants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of separation batteries, and in particular relates to a positive electrode sheet, a battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have become an indispensable energy storage method in mobile electronic devices, electric vehicles and energy storage systems due to their high energy density, long life and good environmental stability. Lithium iron phosphate material (LiFePO4, LFP for short) has become the preferred cathode material for lithium-ion batteries due to its excellent safety, cycle stability and low cost. However, traditional LFP materials still have major bottlenecks in low-temperature performance and fast charging, which limits their widespread application in fast charging and low-temperature environments.

[0003] The existing solutions mainly improve the fast charging performance of LFP materials by optimizing the microstructure and composition of electrode materials. For example, by reducing the size of LFP particles and increasing the specific surface area, the diffusion rate of lithium ions in the electrode is increased, thereby increasing the charging speed; by coating a layer of conductive material, such as carbon or graphene, on the surface of LFP particles to improve the conductivity of the electrode, thereby improving the fast charging performance. In terms of electrolytes, the existing solutions mainly use electrolytes containing high dielectric constant solvents (such as EC, EMC) to improve the ionic conductivity of the electrolyte. In addition, some studies have also tried to add some additives to the electrolyte, such as VC (ethylene carbonate), FEC (fluoroethylene carbonate), etc., to improve the stability and interface properties of the electrolyte.

[0004] Although existing solutions have improved the fast charging performance of LFP materials to a certain extent, there are still some problems and challenges. First, although reducing the size of LFP particles can increase the rate of ion diffusion, it also increases the agglomeration between particles, which will lead to a decrease in the conductivity of the electrode, thereby affecting the overall performance of the battery. Secondly, although surface coating can improve the conductivity of the electrode, the conductivity and stability of the coating material are still limited, especially in high or low temperature environments, the performance of the coating may be significantly reduced. In terms of electrolytes, although high dielectric constant solvents can improve ionic conductivity, they also increase the viscosity of the electrolyte, which will lead to a decrease in the rate of ion diffusion. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a positive electrode sheet, a battery and a preparation method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on both sides of the positive electrode current collector; the positive electrode active material layer comprises a positive electrode active material, a lithium-rich compound, a positive electrode conductive agent, a positive electrode binder and a positive electrode dispersant.

[0008] The mass ratio of the positive electrode active material, lithium-rich compound, positive electrode conductor, positive electrode binder and positive electrode dispersant is (96-96.5): (0.2-0.5): (1-2): (1.5-2.5): (0.1-0.2); preferably 96.1: 0.3: 1.2: 2.2: 0.2.

[0009] The positive electrode active material is lithium iron phosphate, D 50 =0.5~1.05μm, specific surface area =10~12.5m 2 / g, the powder compaction density is ≥2.55g / cm 3 ;

[0010] Preferably, the lithium-rich compound is lithium ferrite, whose molecular formula is Li 5 FeO 4 ;

[0011] Preferably, the positive electrode binder is polyvinylidene fluoride PVDF;

[0012] Preferably, the positive electrode dispersant is an ester polymer; preferably a polycarboxylic acid polyether ester;

[0013] Preferably, the positive electrode current collector is an aluminum current collector;

[0014] Preferably, the positive electrode conductive agent is one of carbon nanotubes and conductive carbon black or a mixture thereof; preferably a mixture of carbon nanotubes and conductive carbon black; the mass ratio of the two is (0.3-0.8): (0.8-1.2), more preferably 0.4:0.8

[0015] The present invention also includes a method for preparing the positive electrode sheet, comprising the following steps: 1) adding positive electrode active material, lithium-rich compound, positive electrode conductive agent, positive electrode binder and positive electrode dispersant to solvent NMP and stirring evenly, adjusting the slurry viscosity and solid content, and finally obtaining a slurry with a viscosity of 4000-12000cp and a solid content of 60-65%; 2) uniformly coating the slurry obtained in step 1) on a current collector and drying it, and then rolling and cutting to obtain the positive electrode sheet.

[0016] The present invention also includes a battery, characterized in that it includes the positive electrode sheet, the negative electrode sheet and the electrolyte.

[0017] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer;

[0018] Preferably, the negative electrode active material layer comprises artificial graphite, a negative electrode conductive agent, a negative electrode binder and a negative electrode plasticizer;

[0019] The mass ratio of artificial graphite, negative electrode conductive agent, negative electrode binder and negative electrode plasticizer is (96.4-97): (0.8-1): (2-2.6): (0.4-1); preferably 96.4: 1: 2.6: 0.5;

[0020] Preferably, the artificial graphite material is composed of a mixture of a single-particle carbonized product and a graphitized product mixed with secondary particles and primary particles, wherein the ratio of the carbonized product is not less than 50%; preferably, the ratio of the carbonized product to the graphitized product is (5-6):(4-5); more preferably, it is 6:4;

[0021] The negative electrode binder comprises CMC, SBR and PAA-Li, wherein the mass ratio of CMC in the negative electrode active material layer is 0.6% to 1%, preferably 0.6%; the mass ratio of SBR is 0.8% to 1%, preferably 0.7%; the mass ratio of PAA-Li is 0.9% to 1.5%, preferably 1.3%;

[0022] Preferably, the negative electrode plasticizer is an alcohol solvent, which is a single alcohol or a composite alcohol;

[0023] Preferably, the negative electrode conductive agent is conductive carbon black.

[0024] The negative electrode sheet is prepared by the following method: 1) adding artificial graphite material, negative electrode conductive agent and negative electrode binder into solvent water and stirring evenly; gradually adding water to adjust the slurry viscosity and solid content, and finally obtaining a slurry with a viscosity of 3000-8500cp and a solid content of 50%-55%; 2) uniformly coating the slurry obtained in step 1) on the negative electrode collector and drying it, and then rolling and cutting to obtain the negative electrode sheet.

[0025] The electrolyte comprises a solvent, an electrolyte and an additive; the solvent comprises ethylene carbonate, dimethyl carbonate and ethyl acetate in a mass ratio of 1.2:1:1.8; the molar concentration of the electrolyte is 0.8-1.2 mol / L; the electrolyte comprises lithium hexafluorophosphate LiPF6 in a mass ratio of 6:1 6 and lithium bis(fluorosulfonyl)imide Li FS I, the additives comprising 3.5% VC and 0.5% FEC in the electrolyte.

[0026] The battery has an energy density of 188Wh / kg, and the available energy at a low temperature of -20°C reaches 80%. It supports up to 3C fast charging, and the capacity retention rate is above 93% after 800 fast charging cycles.

[0027] The present invention also includes a method for preparing the battery, comprising the following steps: using the positive electrode sheet and the negative electrode sheet together, using a separator, and matching the electrolyte to assemble a battery; preferably, the battery is a square aluminum shell battery.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The implementation scheme of the present application improves the cycle life and reduces the impedance through the application of lithium-rich compounds, and improves the homogenization effect through the application of positive electrode dispersants; as a preferred form, the negative electrode sheet achieves fast charging and low cost at the same time through the compounding of carbonized products and graphitized products; the low-density, fast-charging electrolyte improves the energy density and fast-charging performance of the battery; and provides a lithium-ion battery with good low-temperature performance and fast charging using the above-mentioned positive electrode sheet, negative electrode sheet and electrolyte, which can achieve 3C fast charging and has high safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a comparison diagram of fast charging cycles of the embodiment and the comparative example;

[0031] Figure 2 Comparison of DC internal resistance between the embodiment and the comparative example. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0033] Example 1

[0034] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on both sides of the positive electrode current collector; the positive electrode active material layer comprises a positive electrode active material, a lithium-rich compound, a positive electrode conductive agent, a positive electrode binder and a positive electrode dispersant.

[0035] The ratio of positive electrode active material layer is: lithium iron phosphate (D 50 ~1μm, specific surface area~11m 2 / g, powder compaction density ~2.57g / cm 3 ;) 96.1%, lithium-rich compound Li 5 FeO 4 0.3%, carbon nanotubes 0.4%, conductive carbon black 0.8%: positive electrode binder polyvinylidene fluoride PVDF 2.2%, positive electrode dispersant (polycarboxylic acid polyether ester) 0.2%, solvent NMP (nitromethyl pyrrolidone), the obtained slurry viscosity is ~9000cp, solid content is ~63%. The positive electrode slurry is evenly coated on the surface of the aluminum foil, and then rolled and cut to obtain the required positive electrode sheet.

[0036] The negative electrode coating ratio is: artificial graphite 96.4%, (wherein the ratio of carbonized products and graphitized products is 6:4), CMC ratio is 0.6%, SBR ratio is 0.7%, PAA-Li ratio is 1.3%, conductive carbon black ratio is 1%, plasticizer (1,3 butanediol) ratio is 0.5% (considering the volatility of plasticizer, it is not included in the total ratio), the solvent is deionized water, and the resulting slurry finally has a viscosity of ~6000cp and a solid content of about 52%. The negative electrode slurry is evenly coated on the surface of the copper foil, and then rolled and cut to obtain the required negative electrode sheet.

[0037] The electrolyte includes a solvent, an electrolyte and an additive; the solvent includes ethylene carbonate, dimethyl carbonate and ethyl acetate in a mass ratio of 1.2:1:1.8; the concentration of the electrolyte is 1 mol / L; the electrolyte includes lithium hexafluorophosphate LiPF6 in a mass ratio of 6:1 6 and lithium bis(fluorosulfonyl)imide LiFSI, wherein the additive comprises 3.5% by mass of VC and 0.5% by mass of FEC.

[0038] The above-mentioned positive electrode sheet and negative electrode sheet are used together, using a (PE+ceramic+dispensing) separator, and the above-mentioned electrolyte to assemble into a square aluminum shell battery. The single cell capacity reaches 140Ah and the energy density reaches 189Wh / kg.

[0039] Example 2

[0040] In this embodiment, the ratio of the positive electrode coating is: lithium iron phosphate (D 50 ~1μm, specific surface area~11m 2 / g, powder compaction density ~2.57g / cm 3 ;) 96.2%, lithium-rich compound Li 5 FeO 4 0.2%, carbon nanotube ratio is 0.4%, conductive carbon black ratio is 0.8%: binder ratio is 2.2%, dispersant (polycarboxylic acid polyether ester) ratio is 0.2%, solvent is NMP (nitromethyl pyrrolidone), the obtained slurry viscosity is ~9000cp, solid content is about 63%. The positive electrode slurry is evenly coated on the surface of the aluminum foil, and then rolled and cut to obtain the required positive electrode sheet.

[0041] The negative electrode coating ratio is: artificial graphite 96.4%, (wherein the ratio of carbonized products and graphitized products is 5:5), CMC ratio is 0.6%, SBR ratio is 0.7%, PAA-Li ratio is 1.3%, conductive carbon black ratio is 1%, plasticizer (1,3 butanediol) ratio is 0.5% (considering the volatility of plasticizer, it is not included in the total ratio), the solvent is deionized water, the obtained slurry viscosity is ~6000cp, and the solid content is about 52%. The negative electrode slurry is evenly coated on the surface of the copper foil, and then rolled and cut to obtain the required negative electrode sheet.

[0042] The electrolyte includes a solvent, an electrolyte and an additive; the solvent includes ethylene carbonate, dimethyl carbonate and ethyl acetate in a mass ratio of 1.2:1:1.8; the concentration of the electrolyte is 1 mol / L; the electrolyte includes lithium hexafluorophosphate LiPF6 in a mass ratio of 6:1 6 and lithium bis(fluorosulfonyl)imide LiFSI, wherein the additive comprises 3.5% by mass of VC and 0.5% by mass of FEC.

[0043] The above-mentioned positive electrode sheet and negative electrode sheet are used together, using a (PE+ceramic+dispensing) separator, and the above-mentioned electrolyte to assemble into a square aluminum shell battery. The single cell capacity reaches 140Ah and the energy density reaches 188Wh / kg.

[0044] Comparative Example 1

[0045] The difference between Comparative Example 1 and Example 1 is that no lithium-rich compound is added;

[0046] In this embodiment, the positive electrode coating ratio is: 96.4% lithium iron phosphate, no lithium-rich compound is added, the carbon nanotube ratio is 0.4%, the conductive carbon black ratio is 0.8%, the binder ratio is 2.2%, the solvent is NMP (nitromethyl pyrrolidone), the dispersant (polycarboxylic acid polyether ester) ratio is 0.2%, and the solid content of the obtained slurry is about 63%. The positive electrode slurry is evenly coated on the surface of the aluminum foil, and rolled and cut to obtain the required positive electrode sheet.

[0047] The negative electrode coating ratio is: artificial graphite 96.4%, (wherein the ratio of carbonized products and graphitized products is 6:4), CMC ratio is 0.6%, SBR ratio is 0.7%, PAA-Li ratio is 1.3%, conductive carbon black ratio is 1%, plasticizer (1,3 butanediol) ratio is 0.5% (considering the volatility of plasticizer, it is not included in the total ratio), the solvent is deionized water, and the resulting slurry finally has a viscosity of ~6000cp and a solid content of about 52%. The negative electrode slurry is evenly coated on the surface of the copper foil, and then rolled and cut to obtain the required negative electrode sheet.

[0048] The electrolyte includes a solvent, an electrolyte and an additive; the solvent includes ethylene carbonate, dimethyl carbonate and ethyl acetate in a mass ratio of 1.2:1:1.8; the concentration of the electrolyte is 1 mol / L; the electrolyte includes lithium hexafluorophosphate LiPF6 in a mass ratio of 6:1 6 and lithium bis(fluorosulfonyl)imide LiFSI, wherein the additive comprises 3.5% by mass of VC and 0.5% by mass of FEC.

[0049] The above-mentioned positive electrode sheet and negative electrode sheet are used together, a (PE+ceramic+dispensing) separator is used, and the above-mentioned electrolyte is matched to assemble a square aluminum shell battery.

[0050] Comparative Example 2

[0051] The difference between Comparative Example 2 and Example 1 is that no lithium-rich compound is added to the positive electrode and the negative electrode active material is a pure graphitized product;

[0052] In this embodiment, the positive electrode coating ratio is: 96.4% lithium iron phosphate, no lithium-rich compound is added, the carbon nanotube ratio is 0.4%, the conductive carbon black ratio is 0.8%, the binder ratio is 2.2%, the solvent is NMP (nitromethyl pyrrolidone), the dispersant (polycarboxylic acid polyether ester) ratio is 0.2%, and the solid content of the obtained slurry is about 63%. The positive electrode slurry is evenly coated on the surface of the aluminum foil, and rolled and cut to obtain the required positive electrode sheet.

[0053] The negative electrode coating ratio is: artificial graphite 96.4% (pure graphitized products are used), CMC ratio is 0.6%, SBR ratio is 0.7%, PAA-Li ratio is 1.3%, conductive carbon black ratio is 1%, plasticizer (1,3 butanediol) ratio is 0.5% (considering the volatility of plasticizer, it is not included in the total ratio), the solvent is deionized water, and the solid content of the obtained slurry is about 52%. The negative electrode slurry is evenly coated on the surface of the copper foil, and then rolled and cut to obtain the required negative electrode sheet.

[0054] Electrolyte: including solvent, electrolyte and additives; the solvent includes ethylene carbonate, dimethyl carbonate and ethyl acetate in a mass ratio of 1.2:1:1.8; the electrolyte includes lithium hexafluorophosphate LiPF in a mass ratio of 6:1 6 and lithium bis(fluorosulfonyl)imide LiFSI, wherein the additive comprises 3.5% by mass of VC and 0.5% by mass of FEC.

[0055] The above-mentioned positive electrode sheet and negative electrode sheet are used together, a (PE+ceramic+dispensing) separator is used, and the above-mentioned electrolyte is matched to assemble a square aluminum shell battery.

[0056] Comparative Example 3

[0057] The difference between Comparative Example 3 and Example 1 is that no lithium-rich compound is added to the positive electrode and the electrolyte does not contain ethyl acetate and lithium bis(fluorosulfonyl)imide.

[0058] In this embodiment, the positive electrode coating ratio is: 96.4% lithium iron phosphate, no lithium-rich compound is added, the carbon nanotube + conductive carbon black ratio is 1.2%: the binder ratio is 2.2%, the solvent is NMP (nitromethylpyrrolidone), the dispersant ratio is 0.2%, and the solid content of the obtained slurry is about 63%. The positive electrode slurry is evenly coated on the surface of the aluminum foil, and rolled and cut to obtain the required positive electrode sheet.

[0059] The negative electrode coating ratio is: artificial graphite 96.4%, (wherein the ratio of carbonized products and graphitized products is 6:4), CMC ratio is 0.6%, SBR ratio is 0.7%, PAA-Li ratio is 1.3%, conductive carbon black ratio is 1%, plasticizer (1,3 butanediol) ratio is 0.5% (considering the volatility of plasticizer, it is not included in the total ratio), the solvent is deionized water, and the resulting slurry finally has a viscosity of ~6000cp and a solid content of about 52%. The negative electrode slurry is evenly coated on the surface of the copper foil, and then rolled and cut to obtain the required negative electrode sheet.

[0060] Electrolyte: including solvent, electrolyte and additives; the solvent includes ethylene carbonate and dimethyl carbonate in a mass ratio of 1.2:1; the concentration of the electrolyte is 1 mol / L; the electrolyte is lithium hexafluorophosphate LiPF 6 The additive comprises 3.5% VC and 0.5% FEC in a mass ratio.

[0061] The above-mentioned positive electrode sheet and negative electrode sheet are used together, a (PE+ceramic+dispensing) separator is used, and an electrolyte that does not contain ethyl acetate and lithium bis(fluorosulfonyl)imide is used to assemble a square aluminum shell battery.

[0062] The test results of the embodiments and the comparative examples are shown in Table 1. Figure 1 It is a comparison diagram of fast charging cycles of the embodiment and the comparative example; Figure 2 Comparison of DC internal resistance between the embodiment and the comparative example.

[0063] Table 1 Comparison of test results of embodiments and comparative examples

[0064]

[0065]

[0066] The results show that:

[0067] 1) Compared with Example 1 and Example 2, the single cell energy density and the available energy at -20 degrees are slightly different, but the difference is small, and both can achieve 3C fast charging, and the cycle life is basically the same;

[0068] 2) Compared with Example 1, Example 1 has a larger impedance and the available energy at low temperature is about 5% lower. Although it can also meet the 3C fast charge requirement, the cycle life is poor, and the capacity retention rate after 600 cycles is 1% lower.

[0069] 3) Compared with Example 2, the fast charging capability and low-temperature available energy of Example 2 are significantly reduced, and the 3C fast charging cycle is extremely poor, indicating that pure graphitized products cannot support 3C fast charging capability.

[0070] 4) Compared with Example 3, the cycle performance of Example 3 is not significantly reduced, but the monomer energy density is reduced by 3Wh / kg, and the impedance is significantly increased, and the low-temperature available energy is low.

[0071] In summary, the implementation scheme of the present application improves the cycle life and reduces the impedance through the application of lithium-rich compounds, and improves the homogenization effect through the application of positive electrode dispersants; as a preferred form, the negative electrode sheet achieves fast charging and low cost at the same time through the compounding of carbonized products and graphitized products; the low-density, fast-charging electrolyte improves the energy density and fast-charging performance of the battery; and provides a lithium-ion battery with good low-temperature performance and fast charging using the above-mentioned positive electrode sheet, negative electrode sheet and electrolyte, which can achieve 3C fast charging and has high safety performance.

[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode active material layer arranged on both sides of the positive electrode current collector; the positive electrode active material layer comprises a positive electrode active material, a lithium-rich compound, a positive electrode conductive agent, a positive electrode binder and a positive electrode dispersant.

2. The positive electrode sheet according to claim 1, characterized in that: The mass ratio of the positive electrode active material, lithium-rich compound, positive electrode conductor, positive electrode binder and positive electrode dispersant is (96-96.5): (0.2-0.5): (1-2): (1.5-2.5): (0.1-0.2); preferably 96.1: 0.3: 1.2: 2.2: 0.

2.

3. The positive electrode sheet according to claim 1, characterized in that: The positive electrode active material is lithium iron phosphate, D 50 =0.5~1.05μm, specific surface area =10~12.5m 2 / g, the powder compaction density is ≥2.55g / cm 3 ; Preferably, the lithium-rich compound is lithium ferrite, and its molecular formula is Li5FeO4; Preferably, the positive electrode binder is polyvinylidene fluoride PVDF; Preferably, the positive electrode dispersant is an ester polymer; Preferably, the positive electrode current collector is an aluminum current collector; Preferably, the positive electrode conductive agent is one of carbon nanotubes and conductive carbon black, or a mixture thereof; preferably a mixture of carbon nanotubes and conductive carbon black; the mass ratio of the two is (0.3-0.8):(0.8-1.2); more preferably 0.4:0.

8.

4. A method for preparing a positive electrode sheet according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: 1) adding positive electrode active material, lithium-rich compound, positive electrode conductive agent, positive electrode binder and positive electrode dispersant into solvent NMP and stirring evenly, adjusting the slurry viscosity and solid content, and finally obtaining a slurry with a viscosity of 4000-12000cp and a solid content of 60-65%; 2) uniformly coating the slurry obtained in step 1) on a current collector and drying it, and then rolling and cutting it to obtain the positive electrode sheet.

5. A battery, characterized in that: It comprises the positive electrode sheet, negative electrode sheet and electrolyte as described in any one of claims 1 to 3.

6. The battery according to claim 5, characterized in that The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer; Preferably, the negative electrode active material layer comprises artificial graphite, a negative electrode conductive agent, a negative electrode binder and a negative electrode plasticizer; The mass ratio of artificial graphite, negative electrode conductive agent, negative electrode binder and negative electrode plasticizer is (96.4-97): (0.8-1): (2-2.6): (0.4-1); preferably 96.4: 1: 2.6: 0.5; Preferably, the artificial graphite material is composed of a mixture of a single-particle carbonized product and a graphitized product of a mixture of secondary particles and primary particles, wherein the proportion of the carbonized product is not less than 50%; Preferably, the negative electrode binder comprises CMC, SBR and PAA-Li, wherein the mass proportion of CMC in the negative electrode active material layer is 0.6% to 1%, preferably 0.6%; the mass proportion of SBR is 0.8% to 1%, preferably 0.7%; the mass proportion of PAA-Li is 0.9% to 1.5%, preferably 1.3%; Preferably, the negative electrode plasticizer is an alcohol solvent, which is a single alcohol or a composite alcohol; Preferably, the negative electrode conductive agent is conductive carbon black.

7. The battery according to claim 6, characterized in that The negative electrode sheet is prepared by the following method: 1) adding artificial graphite material, negative electrode conductive agent and negative electrode binder into solvent water and stirring evenly; gradually adding water to adjust the slurry viscosity and solid content, and finally obtaining a slurry with a viscosity of 3000-8500cp and a solid content of 50-55%; 2) uniformly coating the slurry obtained in step 1) on the negative electrode collector and drying it, and then rolling and cutting to obtain the negative electrode sheet.

8. The battery according to claim 5, characterized in that The electrolyte includes a solvent, an electrolyte and an additive; the solvent includes ethylene carbonate, dimethyl carbonate and ethyl acetate in a mass ratio of 1.2:1:1.8; the molar concentration of the electrolyte is 0.8-1.2 mol / L; the electrolyte includes lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI in a mass ratio of 6:1, and the additive includes 3.5% VC and 0.5% FEC in the electrolyte.

9. The battery according to claim 5, characterized in that The energy density reaches 188Wh / kg, the available energy at a low temperature of -20°C reaches 80%, it supports up to 3C fast charging, and the capacity retention rate is above 93% after 800 fast charging cycles.

10. A method for preparing a battery according to any one of claims 5 to 8, characterized in that: The method comprises the following steps: using the positive electrode sheet and the negative electrode sheet together, using a separator, and matching the electrolyte to assemble a battery; preferably, the battery is a square aluminum shell battery.